Competencies Possessed by Distance Learners to Access Information Resources in three Distance Learning Federal University Libraries in Nigeria - Ofodu, Patricia Ngozi; Nwachukwu, Victor N (Communicate: Journal of Library and Information Science, 2022)
The study on competencies possessed by Distance Learners to access information resources in three distance learning Federal University Libraries in Nigeria. The study was guided by three research questions that examined the availability of information resources, competencies possessed by distance learners and the challenges militating the retrieval of information resources. The design adopted for this study was descriptive survey. The population of the study was 8,600 learners. The sample size was 38 from UNIABUJA, 33 from DLCABU and 38 from CDLMAUTY. The researcher used a self-developed questionnaire, validated by three experts. The copies of the questionnaire distributed and retrieved were 109. The data collected were analysed using frequency count and simple percentages. Findings from the study reveal that there are some un-available information resources, which could have been of great assistance to the learners. The study also discovered that some learners lack some competencies that hinder their information retrieval. Challenges militating against the effective retrieval of information are lack of adequate information resources, unstable power supply, lack of finance etc. Recommendations made were: there should be provision of fund, create avenue of training for users and provision of alternative power supply etc. for easy retrieval of information resources by distance learners for their academic pursuit.